2014
DOI: 10.5350/dajpn2014270408
|View full text |Cite
|
Sign up to set email alerts
|

Hiperemesis gravidarum tedavisi için göz hareketleri ile duyarsızlaştırma ve yeniden işleme (EMDR) tedavisi: Olgu serisi

Abstract: ÖZETHiperemesis gravidarum tedavisi için göz hareketleri ile duyarsızlaştırma ve yeniden işleme (EMDR) tedavisi: Olgu serisi It is among the most frequent reasons for the hospitalization of pregnant women during prenatal period.There are many factors that cause the development of HG, including psychiatric factors. A lot of women with HG need a psychiatric evaluation and support. It is a challenging disorder for psychiatrists because it does not have a standard clinical diagnostic criteria and a determined psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A number of studies has shown that EMDR is effective in PTSD (4). Some case presentations report that EMDR is also effective in other anxiety disorders, such as panic disorder, phobias, and psychosomatic diseases (5).…”
mentioning
confidence: 99%
“…A number of studies has shown that EMDR is effective in PTSD (4). Some case presentations report that EMDR is also effective in other anxiety disorders, such as panic disorder, phobias, and psychosomatic diseases (5).…”
mentioning
confidence: 99%